Patients’ and nurses’ perceptions of individualised care : an international comparative study - Tsangari, Haritini; Efstathiou, Georgios; Papastavrou, Evridiki (My University, 2012)
Aim. The aim of this study was to compare patients’ and nurses’ perceptions of individualised care in five European countries, the Czech Republic, Cyprus, Finland, Greece and Hungary. Background. Individualised nursing care has been studied from both patients’ and nurses’ perspectives, but to date, there are no studies comparing these perspectives internationally. Methods. A cross-sectional comparative survey design was used. Data were collected from nurses (n = 960; response rate, 79%) and patients (n = 1315; response rate, 78%) in 71 surgical units from 26 acute hospitals in 2009. Data were collected using two Individualised Care Scales (ICS-Nurse and ICS-Patient) and analysed statistically using descriptive and inferential statistics. Results. Differences in patients’ and nurses’ assessments of individualised nursing care were found between each country. Nurses, compared with patients, assessed that they supported patient individuality more often. The Meannurses ranged from 3·61 (SD 0·90, Greece)–4·31 (SD 0·53, Hungary), and the Meanpatients ranged from 3·05 (SD 1·09, Greece)–3·79 (SD 1·00, Cyprus). To a large extent, the care provided was individualised as defined by the Meannurses 3·75 (SD 0·92, Greece)–4·36 (SD 0·49, Hungary) and the Meanpatients 3·41 (SD 0·95, Greece)–4·18 (SD 0·79, Cyprus). In Cyprus and Finland, patients’ assessments of the individuality in their care corresponded well with nurses’ assessments. Clear between-country differences in both patients’ and nurses’ assessments were found in both subscales of the ICS. Conclusions. An in-depth analysis of the European between-country differences is required to define the causes of differences that may be due to the differing content of education, the organisation of nursing work, ideology and values assigned to individualised care and health care systems and processes in each country. Relevance to clinical practice. Obtaining both patients’ and nurses’ assessments of individualised care may facilitate the further development of individualised nursing care and be used to help to harmonise European health care processes and nursing care.
Keywords: International; Nursing; Survey; Nurse and patient